Risk and Reliability Analysis of Substation Protection Systems Using a Probabilistic Approach - Putri, Adinda (Journal of Electrical Engineering, 2024)
The reliability of a substation protection system is crucial for maintaining the continuity of power supply and reducing the risk of equipment damage due to external disturbances, such as lightning or operational errors. However, in practice, protection systems are often affected by uncertainties that can affect system performance. This study aims to analyze the risk and reliability of a substation protection system using a probabilistic approach to assess the impact of uncertain variables on system performance. This approach combines Monte Carlo simulation to generate event probability distributions and a multi-objective optimization algorithm to determine the optimal arrester location and capacity. Simulation results indicate that the probabilistic approach provides a more realistic picture of protection system performance under uncertain conditions compared to traditional deterministic methods. Furthermore, this study identifies the trade-offs between risk reduction and investment costs required for protection optimization, and provides recommendations for more efficient and accountable protection investment policies. These findings can serve as a reference for electric utilities in designing more reliable and cost-effective substation protection systems.